Accumulation of trace metals in green mussel Perna viridis in the shellfish harvesting environment along southern Karnataka coast - Sasikumar, Geetha; Krishnamoorthy, M.; Krishnakumar, P. K.; Bhat, G. S. (Indian Journal of Fisheries, 2011)
The levels of trace metals, Cd, Pb, Cu, Zn, Ni and Fe in seawater and their bioaccumulation in green mussel Perna viridiswere examined in two shellfish harvesting environments, Someshwara and Surathkal, along the southern Karnataka coast.In seawater, the concentration of trace metals analysed were below the levels causing harmful effects on the larvae and adultmussels, set by the European Council Directive 79/923/EEC. The Fe, Ni, Cd and Zn levels in mussel tissue from Surathkalwere relatively higher when compared to that of mussel tissue samples from Someshwara while Cu and Pb levels were lower.The mean tissue concentrations of trace metals in the soft tissue of P. viridis from shellfish waters were found to be safe andbelow the permissible concentrations for seafood (US FDA and WHO) as well as EU limits in marine products.